Feasibility of a 12-Week, Therapist-Independent, Smartphone-Based Biofeedback Treatment for Episodic Migraine in Adults: Single-Center, Open-Label, 1-Armed Trial - Amalie Christine Poole; Ingunn Grøntveit Winnberg; Melanie Rae Simpson; Anker Stubberud; Kjersti Grøtta Vetvik; Marte-Helene Bjørk; Lise Rystad Øie; Petter Holmboe; Alexander Olsen; Erling Tronvik; Tore Wergeland (JMIR Human Factors)
Abstract BackgroundBiofeedback is an established treatment principle for migraine, but home-based therapy with proven efficacy is not available. ObjectiveThis study aims to assess the feasibility, usability, and safety of 12 weeks of daily use of a novel medical device (Cerebri; Nordic Brain Tech AS) for therapist-independent multimodal biofeedback preventative treatment in adults with episodic migraine. MethodsIn this open-label, one-armed trial, 20 adult participants with episodic migraine used Cerebri for 12 weeks. The primary outcome was the feasibility of the Cerebri system, measured by the level of adherence to daily biofeedback and electronic headache diary (eDiary) entries. Secondary outcomes were safety, usability, and efficacy. ResultsInitial adherence to biofeedback was high (16/20, 80% in weeks 1‐4), declining to 20% (4/20) by weeks 9‐12. eDiary adherence remained high (15/20, 75% in weeks 9‐12). Reduction in migraine days was not significant (–0.6, 95% CI –2.4 to 1.1 days; P ConclusionsCerebri demonstrates potential in self-managed migraine treatment, with strong initial engagement and high safety. Usability issues, including technical bugs, were identified as the most important modifiable cause for the decline in adherence. This highlights the need for further app refinement to sustain user engagement.